Avaliação do hábito intestinal de lactentes em aleitamento materno exclusivo - MENEZES, Iara Fernandes (2023)
The breast milk is essential for the health in the first six months of life, being complete and perfectly well-adjusted to the metabolism of the child. The WHO recommends breast-feeding exclusively, in first four to six months of life. In Brazil, the Ministry of Health recommends the exclusive breast-feeding in the first six months of life. Has been noticed that the absence of breastfeeding or its precocious interruption and the introduction of other types of foods in the diet of the child have been frequent, with potentially harmful consequences to the health of the child, such as intestinal constipation. In milk-fed infants this frequency is lifted up and on the breastfed, it varies widely from an evacuation at each seven / ten days up to ten or more evacuations / day. In children receiving exclusively breast milk, the intestinal habit can also vary, and in most of them, the evacuations being superior to three days time, from one to another, but with elimination of normal feces, characterizing intestinal false constipation. Considering the lack of data on the predominance of false constipation I n our region and aiming a better knowledge of the children´s intestinal habits on exclusively breastfeeding, a cross study happened in the outpatient department of child care of the HFSCMPA, with 200 children with less than six months old, receiving breast milk exclusively. The data were collected on age, weight, stature, sex, interval between the evacuations, number of evacuations per day and consistency of the feces and inserted into the EPI INFO program, version 6.04 for statistical analysis. The charts and graphs were made in Microsoft Excel 2003. For analysis of significance was used the t-Student test, comparison of the difference between the averages in each month of life, with a = 0.05 level (5%), through BioEstat 5.0 software, marked with an asterisk (*) the significant values. The age ranged from 0 to 6 months with the largest number of patients with 1 month of life in relation to the number of evacuations, the prevalence was 1 to 3 evacuations/ day, corresponding to 60% of patients within the sample. The interval between the predominant evacuation was less or equal to three days, corresponding to 85.5% of patients. The consistency of the feces in almost its entirety was pasty or liquid (98.5%). The false constipation was diagnosed in 29 patients (14.5%) being most prevalent between the 2nd and 4th month of life. The average was 3.6 evacuations per day, and distributed by age group was higher in population with a month old. The overall interval average between the evacuations was 2.5 days and distributed by age, being higher in the fourth and sixth month, the months of greatest prevalence of intestinal false constipation in the population studied. In the first semester of life, it was found that lack of breastfeeding is a factor associated with constipation. The number of evacuations is greater in the first semester of life, and decreases with increasing age. The frequency of evacuations in milk-fed infants on breastfeeding is higher than in the artificial feeding. The breastfeeding should be considered a protective factor against the development of constipation in the first six months of life.